Exploring Gender Differences in Academic Burnout Among Junior High School Students - Sabila, Intan Ayu; Mahdi, Hilmi; Pinandasari, Julia Pande; Rahman, Diniy Hidayatur; Afrikatin, Sri Asia (Universitas Negeri Malang, 2024)
This study explores the differences in academic burnout levels between male and female eighthgrade students at SMPN 3 Batu. Utilizing a comparative design, the research involved 137 students, including 39 males and 98 females, with data collected through the Indonesian version of the School Burnout Inventory (SBI). Independent sample t-tests were employed for data analysis. The results indicated no significant gender differences in academic burnout levels, as both male and female students exhibited similar experiences of burnout as indicated by Sig. (2-tailed) value of 0.432. The majority of students reported moderate levels of burnout, with 70.1% of the sample falling into this category. Furthermore, 16.1% of the students experienced low burnout, while 13.9% reported high burnout levels. The findings underscore the prevalence of academic burnout among junior high school students, emphasizing the need for interventions that cater to the needs of all students regardless of gender. This research contributes to the body of knowledge on academic burnout by focusing on younger adolescents, a demographic often overlooked in burnout studies. The study highlights the importance of early identification and intervention to prevent and manage academic burnout, ultimately supporting students' mental health and academic success.